Residential immersive life skills programs for youth with disabilities: a case study of youth developmental trajectories of personal growth and caregiver perspectives - Shauna Kingsnorth; Alanna E. F. Rudzik; Gillian King; Amy C. McPherson (BMC, 2019)
Abstract Background Professional support in pediatric and rehabilitation care environments has been recommended as a means to build youth competence in life skills during their transition to adulthood. Life skills are the essential psychosocial competencies and interpersonal skills needed to manage one's life. Residential immersive life skills (RILS) programs offer youth with physical disabilities enriched learning environments to acquire these skills. This study explored trajectories of personal growth in life skills and positive psychological outcomes among youth participating in a RILS program and related caregiver perspectives. Method Delivered by a multidisciplinary healthcare team, The Independence Program is an intensive summer program housed in a college residence that provides realistic experiences of living away from home for small groups of youth between 17 and 21 years of age who have congenital and/or acquired physical disabilities. Using a longitudinal case study and qualitative descriptive design, four youth and their parents/guardians participated in semi-structured interviews prior to, and then 1 month, and 3 to 4 months after the program. A conventional content analysis yielded chronological narratives for each youth and caregiver dyad of their experiences, perceptions and outcomes over time. These narratives were further summarized using a 'line of development' perspective to describe individual developmental trajectories of personal growth. Results All four of the youth returned from the program with positive reports about the new life skills acquired and new behaviours they engaged in. These positive reports generally continued post-program, albeit with differing trajectories unique to each youth and varying levels of congruence with their caregivers' readiness to support, accommodate and facilitate these changes. Caregivers differed in their capacity to shift in their parenting role to support consolidation of youth life skill competencies following program participation. Conclusions RILS programs can be transformative. Varied youth trajectories identified significant personal growth through enhanced self-determination, self-efficacy and self-advocacy. Congruence in youth and caregiver perceptions of post-program changes was an important transactional factor. Professional support addressing caregiver needs may be beneficial to facilitate developmentally appropriate shifts in parenting roles. This shift is central to a model of shared management whereby adolescents take on greater responsibility for their own care and life choices.